Kemampuan Berpikir Analisis Siswa melalui Strategi Pemberian Feedback Pembelajaran Sistem Ekskresi: - - Yuni Astuti; Siti Aulia Febrianti; Budhi Akbar; Luthpi Safahi (BIOEDUSCIENCE, 2021)
Background: The ability to think analytically is one part of higher-order thinking skills, which should be owned by students according to the reference in the curriculum. Giving feedback is one of the efforts to support students' analytical thinking skills. Methods: The research used is Quasi-Experimental, with a Posttest-Only Control Design. The sampling technique used was Cluster Random Sampling. The research instrument was used through a test in the form of a description of 6 questions integrated into three indicators of analytical thinking ability (Differentiating, Attributing and Organizing). Results: showed that the average value of posttest analytical thinking ability in the experimental class was 63.67, which was greater than the control class, which was 56.63. Hypothesis testing through t-test at the 5% significance level obtained the value of tcount = 2.13 while ttable = 2.00, it is mean that tcount > ttable then H0 is rejected. Conclusions: The conclusion that can be formulated is that giving feedback has a significant effect on students' analytical thinking skills on the excretory system material, with the highest achievement indicator of analytical thinking ability achieved by indicators attributing.